Kebutuhan Perawat Puskesmas Berbasis Analisis Beban Kerja - Harisa Laraswatie; Tjahjono Kuntjoro; Sutopo Patria Jati (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2016)
A nurse’s necessity at a health centre viewed from workload analysis is required to identify a nurse’s necessities adjusted with service standards and real condition at a health centre. This requirement is in accordance with the change of an outpatient health centre status to be an inpatient health centre in which infrastructure and human resource need to be improved. This was a qualitative study using case study approach started from data collection, FGD, NGT, work sampling, to indepth interview with stakeholders who had experiences in calculating an employee’s necessities based on ABK and nurse representative. Furthermore, data were analysed using a form to calculate an employee’s necessities obtained from BKN. The results of calculation of a nurse’s necessities showed that number of nurses required for an inpatient unit were nine persons consisted of five skilled nurses and four expert nurses. This number was equal to nine beds that were required (1:1). On the other hand, number of nurses required for an outpatient unit including BP, UKM, and Pustu were 26 persons (16 skilled nurses and 10 expert nurses) or 1 nurse served 1,458 people or 456 families. Rembang 2 Health Centre needs to fulfil a nurse’s necessities by considering innovation of nursing services to reduce burden of human resource. A nursing committee needs to be formed by District Health Office as an institution that is responsible to supervise functional positions. Standards of nursing diagnosis and an information system of nursing care services need to be determined in order to describe an autonomy level of individual, family, group, and community in District of Rembang in terms of self-care. In addition, academics need to conduct further research regarding workload of other functional positions in health in order to achieve goals of national health development.